Resveratrol supplementation rescues pool of growing follicles and ovarian stroma from Cisplatin-induced toxicity on the ovary in Sprague-Dawley rats: An experimental study - Gbotolorun Stella Chinwe; Okafor Izuchukwu Azuka; Ndoeche Chidinma Adaeze (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Cisplatin is a potent antineoplastic agent for many cancers but causes several levels of gonadal damage. Ovarian toxicity is a major concern of young cancer patients undergoing chemotherapy. Objective: This study sought to examine the effect of Cisplatin and Resveratrol supplementation on ovarian function in Sprague-Dawley rats. Materials and Methods: In this experimental study, 45 cyclic Sprague-Dawley rats with an average weight of 160 gr were divided into 9 groups (n=5/group). Group 1 was used as control and received distilled water. Groups 2 and 9 received Cisplatin only. Groups 3, 4, and 5 received different doses of Resveratrol after a single dose of Cisplatin. Groups 6, 7, and 8 received Resveratrol before Cisplatin. At sacrifice, the ovary was analyzed for histopathology, biochemical indices of oxidation and hormonal assay. Results: Relative and absolute organ weights were notably increased (p=0.001, 0.01) in the prophylactic groups relative to the groups that received Resveratrol after Cisplatin. Also, glutathione, superoxide dismutase and catalase were significantly increased (p=0.047, 0.01, 0.023) in a dose-dependent manner when compared to Cisplatin group only. Malondialdehyde decreased significantly (p=0.001) in the groups that received high dose Resveratrol compared with the control and Cisplatin alone groups. Although oestrogen showed no significant difference within the groups (p=0.48), Resveratrol significantly increased progesterone, follicle stimulating hormone and luteinizing hormone levels (p=0.007, 0.001, 0.006) at high doses when compared with Cisplatin alone groups. Ovarian histoarchitecture was best preserved in the prophylactic groups in a dose-dependent manner. Conclusion: Resveratrol supplementation confers protection and preserves ovarian follicles from Cisplatin toxicity in Sprague-Dawley rats.